Contiguity, connectivity and access : the importance of the Bay of Bengal Region in Indian foreign policy - Das, Suranjan; Sengupta, Anita; Indian Council of World Affairs (New Delhi : KW, 2022)
This volume examines themes like contemporary factors shaping the emergence of the Bay of Bengal region as a critical strategic theatre in Indian foreign policy; the inter-connectedness of the Indian and Pacific Oceans; the importance of oceans to security and commerce and India$1 (Bs role within the broader region; the twenty-first century maritime Silk Road and Indian alternatives and the possibilities of reconnecting disconnected spaces through re-imagining a Bay of Bengal Community. In this connection the volume takes particular note of the emerging regional cooperative order for the promotion of peace and development in the Bay of Bengal region (BIMSTEC). The volume brings together historians, political analysts and political economists to emphasize the interconnectedness of the oceanic space through a detailed analysis of the Bay of Bengal as a space of strategic and economic significance, particularly for India, but also as a space for re-imagining a new regional community.s
Contributed articles.
Indian Council of World Affairs, New Delhi.
Includes bibliographical references.
English.
Keywords: Geopolitics -- Bengal, Bay of; Bengal, Bay of -- Strategic aspects